1991
DOI: 10.1523/jneurosci.11-11-03594.1991
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanism of Ca2+ current inhibition produced by serotonin in rat dorsal raphe neurons

Abstract: Calcium currents and their modulation by 5-HT were studied using both whole-cell and single-channel patch-clamp techniques in acutely isolated adult rat dorsal raphe neurons. Evidence for three types of Ca channels (T, N, L) was obtained in both whole-cell and single-channel experiments. Approximately 4% of the total high-threshold Ca current (L-type) was sensitive to dihydropyridines (DHPs) while approximately 40% of the Ca current (N-type) was sensitive to omega-conotoxin (omega-CgTx). About 56% of the whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
3
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 57 publications
10
111
3
1
Order By: Relevance
“…Squares, Control; filled circles, 5-HT (1 M). (Bayliss, 1995), or N-type currents in sensory neurons (Del Mar et al, 1994) and other C NS neurons (Pennington et al, 1991;Koike et al, 1994). Consistent with these reports, our results showed that N-and P/Q-type H VA C a 2ϩ current was inhibited by 5-HT in R-B neurons.…”
Section: Modulation Of the T-type Currentssupporting
confidence: 93%
See 2 more Smart Citations
“…Squares, Control; filled circles, 5-HT (1 M). (Bayliss, 1995), or N-type currents in sensory neurons (Del Mar et al, 1994) and other C NS neurons (Pennington et al, 1991;Koike et al, 1994). Consistent with these reports, our results showed that N-and P/Q-type H VA C a 2ϩ current was inhibited by 5-HT in R-B neurons.…”
Section: Modulation Of the T-type Currentssupporting
confidence: 93%
“…The 5-HT 1A receptor can inhibit Ca 2ϩ entry through HVA channels into afferent terminals of nociceptors in mammalian spinal cord (Del Mar et al, 1994). 5-HT 1A receptors also have been reported to be involved in the voltage-dependent G-protein-coupled inhibition of the HVA currents in other CNS neurons (Pennington et al, 1991;Koike et al, 1994;Bayliss et al, 1995;Foehring, 1996). Unlike these previous reports, the inhibition of the HVA currents by 5-HT 1A receptors in Xenopus R-B neurons is not voltage-dependent.…”
Section: Identity Of Serotonergic Receptorsmentioning
confidence: 69%
See 1 more Smart Citation
“…There is general consensus that this involves a direct effect of the activated G-protein subunit or subunits on the calcium channel itself, and recent evidence indicates a key role for the G-protein ␤␥ subunits (Herlitze et al, 1996;Ikeda, 1996). The inhibition exhibits characteristic gating shifts manifested as slowed activation kinetics, a diminution of the inhibition at positive membrane potentials, and partial relief from inhibition by conditioning prepulses (Bean, 1989;Elmslie et al, 1990;Penington et al, 1991). These effects have been incorporated into models in which the channels exhibit two functional gating states, one in the presence ("reluctant") and another in the absence ("willing") of inhibition (Bean, 1989;Elmslie et al, 1990;Boland and Bean, 1993;Golard and Siegelbaum, 1993).…”
Section: Abstract: Calcium Channel; G-protein; Atp; Inhibition; Patcmentioning
confidence: 99%
“…This would be achieved if there were relief from inhibition during trains of action potentials. However, use of short depolarizing steps to mimic action potentials suggests that for N-type channels this may be confined to cells capable of firing at very high rates (Penington et al, 1991;Williams et al, 1997). Relief of P/Q-type channel inhibition by action potentials may depend on the duration of the action potential waveform (Brody et al, 1997).…”
Section: What Accounts For the Differential Inhibition Of The Two Chamentioning
confidence: 99%